Virtuous Leadership: An Agenda for Personal Excellence - "Havard, Alexandre" (New York, 2014)
Virtuous Leadership: An Agenda for Personal Excellence is a book by Alexandre Havard. It sets forth a leadership model to help professional people grow in virtue and lead effectively. Virtuous Leadership has been translated into 15 languages including Russian and Chinese.
Keywords: Leadership-Moral and ethical aspects